Kinematic analysis of the power position and delivery phase for the O`Brien and standing throw shot put techniques - Singh, T.; Mei Kay, L.; Koh, M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of the study was to examine the kinematic variables of the power position phase for the O`Brien and standing throw techniques used by competitive school athletes so as to gain insights into any technique differences amongst the kinematic variables of the power position between the two techniques and also study whether school athletes are able to capitalize on the biomechanical advantages of the O`Brien technique over the standing throw technique. Three female competitive school athletes were recruited for the study. Each subject performed 4 trials of the throws for each technique. Data was captured using the Peak camera systems operating at 50 Hz and 1/500 shutter speed. Maximal effort was stressed and only the best trial was taken for analysis for each technique per subject. The study showed that the athletes did not effectively capitalize on the biomechanical advantages of the O`Brien technique for maximizing their throw distance.